2019
DOI: 10.24925/turjaf.v7isp3.11-16.3094
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Antioxidant Variability of Some Wild and Cultivated Edible Mushrooms from Kastamonu Rural Areas

Abstract: In this study, variation of some chemical components such as anthocyanin, β-carotene, lycopene, phenolic, nitrate, soluble protein, proline, glucose, sucrose and total carbohydrate level ad PAL activity in some wild and cultivated edible mushrooms was examined. For this, four different mushroom species (Agaricus campestris L., Cantharellus cibarius Fr., Hericium erinaceus (Bull.) Pers., Lactarius piperatus L. Pers) were supplied from local market, named Kuzeykent Semt Bazaar, in Kastamonu province of Turkey. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The results showed that PAL activity varied in the different organs of the mushroom. Turfan et al (2019) determined that PAL activities ranged between 5.79-6.99 EU mg -1 in different mushroom species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that PAL activity varied in the different organs of the mushroom. Turfan et al (2019) determined that PAL activities ranged between 5.79-6.99 EU mg -1 in different mushroom species.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, parasol mushrooms are effective to prevent oxidative damage due to tocopherols, polyketides, steroids, terpenes, vitamins C and A, flavones, and β-carotene they have (Rao and Rao, 2007;Robaszkiewicz et al, 2010). Turfan et al (2019) investigated the anthocyanin, β-carotene, lycopene, phenolic, nitrate, soluble protein, proline, glucose, sucrose, and total carbohydrate levels and PAL activity of some mushrooms (Agaricus campestris, Cantharellus cibarius, Hericium erinaceus, and Lactarius piperatus).…”
Section: Introductionmentioning
confidence: 99%